MHD squeezing flow of nanoliquid on a porous stretched surface: numerical study - M. Fayyadh, Mohammed; Roslan, R.; Kandasamy, R.; Ali, Inas R. (Asian Research Publishing Network, 2019)
This work is aimed at conducting a comparative study between two base fluids water as well as ethylene glycol along with nanoparticle (oxide aluminium). Analysis is done for determining unsteadiness between two parallel walls, wherein squeezing of upper wall towards lower is done, while porous stretching surface is lower. The mathematical formulation uses constitutive expression pertaining to viscous nanoliquids. By keeping a variable magnetic field, conduction of nanoliquid is done electrically. The partial differential equations concerning the issue were resolved after transforming to ordinary differential equations by employing forth-fifth Runge-Kutta Fehlberg method. The effect of disparity in various parameters pertaining to temperature, velocity and concentration profile of nanoparticle is first plotted and then tabulated. Based on the obtained results, the velocity field was seen to enhance with rise in squeezing parameter values. Squeezing parameters that possess larger values result in decrease in temperature and concentration profiles of nanoparticles. The heat transfer of nanoliquids was seen to improve with squeezing flow, magnetic field parameter and nanoparticle volume fraction. For the rate of skin friction pertaining to ethylene glycol and water, dominance was seen for magnetic parameter M, suction parameter S and nanoparticle volume fraction parameter.